Flow characteristics of the Hornád River and the anthropogenic impact of the Ružín dam for the period 1973–2020 - Nagy, Patrik; Kubiak-Wójcicka, Katarzyna; Káposztásová, Daniela; Zeleňákova, Martina; Vranay, František (Frontiers in Environmental Science, 2023)
The aim of the study is to analyse the monthly and annual variability of the flow of the Hornad River in the years 1973-2020. The research showed that an upward trend in annual air temperature, precipitation and flows was recorded throughout the catchment area. The analysis of the annual Richard-Baker Index (RBI) and flow variability (Cv) showed a clear downward trend in the variability indexes Cv and RBI in the analyzed multi-year period only at the Kysak station, which is located downstream of the dam. No such changes were observed at the remaining Margecany and Spisska Nova Ves stations, which are located above the dam. The analysis of average monthly RBI values over the course showed greater variation. Between 1973 and 2020, the RBI values ranged from 0 to 0.49 at the Spisska Nova Ves and Margecany hydrological stations, while at the Kysak station, the RBI ranged from 0 to 0.57, indicating large changes in short-term flows. The study uses the flashiness index developed by Richard-Baker, called RBI. The results indicate that greater variability of the RBI index on an annual and monthly basis was recorded at the Kysak station located below the below the Ružín Dam. The maximum RBI value occurred in in June 1973 (0.57) at the Kysak station. At the hydrological stations above the Ruzin reservoir, the maximum RBI values were recorded in as well as in July 2008 (0.49) at the Margecany station (0.49) and at the Spisska Nova Ves station (0.48), which was the result of very high precipitation (above 170 mm during a month). The values of the RBI at the Kysak station depended on the possibility of water retention in the Ružín I and Ružín II reservoirs and flow control below the dam.